ENGINEERING ZnO/BIOCHAR COMPOSITES FOR ENHANCED PHOTOCATALYTIC PERFORMANCE: MECHANISTIC ELUCIDATION OF TETRACYCLINE DEGRADATION AND UV–VIS SPECTROSCOPY-BASED KINETIC ANALYSIS - Saddam Husein; Fatma Aris Setiawan; Candra Saka Nusantari (Jurusan Kimia FMIPA Universitas Lampung, 2026)
Tetracycline contamination in aquatic environments is difficult to remove using conventional treatment methods due to its stable and persistent nature. This study aimed to develop ZnO/Biochar composites and evaluate their photocatalytic activity for tetracycline degradation. Laboratory experiments were conducted by varying catalyst dosage and UV–Vis irradiation time. Tetracycline concentration was monitored using UV–Vis spectrophotometry at 378 nm. Catalyst dosage of 0.5 g provided optimum performance, achieving 84% degradation efficiency after 120 min of irradiation. Increasing catalyst dosage up to the optimum level improved degradation efficiency, whereas excessive amounts reduced effectiveness due to increased turbidity. Kinetic analysis indicated that the degradation followed a pseudo-first-order model with a rate constant of 0.0142 min⁻¹. These findings demonstrate that ZnO/Biochar composites have potential as photocatalytic materials for antibiotic wastewater treatment.